K-Ar dating, geological and paleomagnetic study of a 5-km lava succession in northern Iceland (Dataset) ... - Saemundsson, Kristjan; Kristjansson, Leo; McDougall, Ian; N. D. Watkins (Magnetics Information Consortium (MagIC), 2007)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: K-Ar dating, geological and paleomagnetic study of a 5-km lava succession in northern Iceland ...